1994
DOI: 10.1271/bbb.58.475
|View full text |Cite
|
Sign up to set email alerts
|

Application of Solution Thermodynamics to the Water Sorption Isotherms of Food Materials

Abstract: Solution thermodynamics was applied to the water sorption isotherms of foods. First, we corrected Le Ma:~uer's theory. By this correction, it was found that the same thermodynamic equations were applicable to both water sorption data measured at constant total pressure (P) and to those measured under the particular vapor pressure, P = Pw' for a food material. Second, the change in the water sorption behavior of rrce flour by defatting and extrusion cooking was analyzed by solution thermodynamics. It was confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…(5) by using the water sorption isotherm. Parameter LtG: can be evaluated analytically, if the water sorption isotherm fits well with the GAB (Guggenheim, Anderson, and de Boer) equation as in the studies of Le Maguer 1 ) and Kumagai et al 2) However, the water sorption isotherms obtained in this study did not fit well with the GAB equation, especially in the region of high water activity. Therefore, parameter LtG!…”
Section: Evaluation Of Ltg: Ltg;~ and Ltgsmentioning
confidence: 78%
See 3 more Smart Citations
“…(5) by using the water sorption isotherm. Parameter LtG: can be evaluated analytically, if the water sorption isotherm fits well with the GAB (Guggenheim, Anderson, and de Boer) equation as in the studies of Le Maguer 1 ) and Kumagai et al 2) However, the water sorption isotherms obtained in this study did not fit well with the GAB equation, especially in the region of high water activity. Therefore, parameter LtG!…”
Section: Evaluation Of Ltg: Ltg;~ and Ltgsmentioning
confidence: 78%
“…(7) can be used when the measurement is done at constant pressure, i.e., with inert gas. However, as Kumagai et al 2) have discussed, the second term on the right side of Eq. (6) is negligible if the swelling ratio, VS/( Vw + V aO ), is about unity.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Le Maguer 12 ) has applied solution thermodynamics to the water sorption isotherms of potato starch. Kumagai et al 13) have corrected the errors in the theory of Le Maguer's paper and applied the modified theory to the water sorption isotherms of defatted and extruded rice flour: they have shown that the "integral Gibbs free energy" physically means the change in Gibbs free energy by water sorption and that it was an appropriate parameter for evaluating the affinity of food for water. As a result, the enhanced affinity of rice flour for water after defatting and extruding was quantitatively evaluated by solution thermodynamics.…”
mentioning
confidence: 99%